The Way We Teach Now: Exploring Resilience and Teacher Identity in School Teachers During COVID-19 - Ramakrishna, Madhumita; Singh, Purnima (Frontiers in Education, 2022)
With the sudden onset of the COVID-19 pandemic, teachers across the globe felt the need to respond overnight to unprecedented adversity. Rapid adaptation to unfamiliar modes of teaching was required, leading teachers to face overwhelm on two fronts–adapting to a global pandemic, and teaching in the absence of resources and infrastructure. The lack of a physical classroom and face-to-face interaction also impacted a teachers’ sense of purpose and identity. Shifts in teacher identity affect their motivation, commitment, job satisfaction, and self-image, which collectively influences their resilience. By focusing on the impact of COVID-19 on their teaching experience, this study attempted to understand the resilience of the teaching community while exploring the social and emotional factors that helped them adapt. Using the Life Story Interview method, 20 school teachers in the Delhi National Capital Region were asked to reflect on their teaching experiences during the lockdown to explore their resilience in adapting to a new reality. Reflexive thematic analysis revealed adjustment to change and loss, disengagement, and recognising small victories as themes.